Hijab & the Republic: Uncovering the French Headscarf Debate - Scott, Joan W. (A journal of church and state, 2009)
In recent years, arguably no issue has as dramatically raised the question of the relation between religion and state policy as the French headscarf controversy. The issue of whether young girls could attend state schools wearing the hijab roiled French society from at least 1989 (the bicentennial of the French Revolution) until a law passed in 2004 forbidding “conspicuous” signs of religious affiliation. The law did not fully resolve the matter of what constitutes appropriate dress in this strongly secular society. In the spring and summer of 2009, a heated discussion of burqas—the full-body covering worn by a small minority of Muslim women in France—set things off again, with the President of the Republic declaring that “the burqa will not be welcome on French territory.